Pengaruh Penerapan Metode Pembelajaran Karya Wisata terhadap Motivasi Belajar IPS di SD - Riski Fauzi Amelia; Shafarina Nidaul Aulia; Tin Rustini (Journal on Education, 2022)
Every subject requires creativity from educators, as well as social studies subjects. Not a few monotonous learning offered by the teacher in learning causes a lack of motivation to learn for students. Therefore, this study aims to determine the effect of the field trip learning method on social studies learning motivation in elementary schools. The research method uses qualitative methods with literature study. With the result that the field trip learning method is very influential on social studies subjects in elementary schools, it is proven by the application of this method to make students more active and able to achieve the goals of the learning given. Students can receive new experiences, even new information that is not obtained in class. With the field trip method, students can search for and find lessons related to the material that has been determined, thus giving a different impression to students. This is what can lead to student learning motivation when the field trip method is implemented, and can have a positive influence on students and teachers when applying it.